Placebo response in binge eating disorder. - Jacobs-Pilipski, M; Wilfley, D; Crow, S; Walsh, B; Lilenfeld, L; West, D; Berkowitz, R; Hudson, J; Fairburn, C (2007)
OBJECTIVE: Placebo response in studies of binge eating disorder (BED) has raised concern about its diagnostic stability. The aims of this study were (1) to compare placebo responders (PRs) with nonresponders (NRs); (2) to investigate the course of BED following placebo response; and (3) to examine attributions regarding placebo response. METHOD: The baseline placebo run-in phase (BL) was part of a RCT investigating sibutramine hydrochloride for BED; it included 451 participants, ages 19-63, diagnosed with BED. Follow-up (FU) included 33 PRs. RESULTS: : In this study, 32.6% of participants responded to placebo (PRs = 147; NRs = 304). PRs exhibited significantly less symptom severity. At FU (n = 33), many PRs reported continued symptoms. CONCLUSION: PRs exhibited significantly less severe pathology than NRs. Placebo response in BED may transitory or incomplete. The results of this study suggest variable stability in the BED diagnosis.